Aortico-left ventricular tunnel and left ventricular non-compaction: a case series. (22nd June 2015) - Smith, Brandon M.; Cochran, Clinton D.; Owens, Sonal T.
Abstract: Aortico-left ventricular tunnel and left ventricular non-compaction are rare congenital cardiac anomalies with varied clinical presentations and sparsely described co-existence in the medical literature. Owing to the limited information about these diagnoses in tandem, we present four cases of aortico-left ventricular tunnel and left ventricular non-compaction from our institution and discuss the clinical presentation, management, and follow-up.